Experimental study of the dielectronic recombination into Li-like uranium. (26th November 2015) - Trotsenko, S; Gumberidze, A; Gao, Y; Kozhuharov, C; Fritzsche, S; Beyer, H F; Hagmann, S; Hillenbrand, P-M; Petridis, N; Spillmann, U; Surzhykov, A; Thorn, D B; et al.
Abstract: We have measured the x-rays following 116.15 MeV u −1 collisions with H2 at 35°, 90°, 120° and 150° observation angles with regard to the ion beam direction. From our experimental spectra combined with radiative electron capture calculations, we obtain angular distribution of characteristic x-rays (L K) following the resonance transfer and excitation. Our result shows a good qualitative agreement with theoretical predictions.